Chitin binds more cholate than chitosan - Herrera, Flora Patricia (1996)
Chitosan (deacetylated chitin) is known to exert hypocholesterolemic activity and decreases hepatic cholesterol and Triacylglycerol in experimental animals (Hirano et al. 1990. Knorr 1991. Ikeda el al. 1993. Le Houx & Grondin 1993). The ability of Ihis insoluble polymer to sequester hile sahs leads 10 a blockade of Iheir enlerohepalic recycling. This results in Ihe decrease 01 circulating levels of blood cholesterol. because The fecal loss of bile constituents demands an increase in the hepatic Transformation of cholesterol into bile acids.